PENGARUH BIMBINGAN BELAJAR GANESHA OPERATION TERHADAP PRESTASI UJIAN NASIONAL SISWA SMA NEGERI 7 BANJARMASIN TAHUN AJARAN 2014/2015 - Fitri Heldayanti; Parida Angriani; Sidharta Adyatma (JPG (Jurnal Pendidikan Geografi), 2015)
Title in this research is “The Influence of Tutoring Ganesha Operation to The Student National Examination Achievement SMA Negeri 7 Banjarmasin Academic Year 2014/2015”. This research aims to find out the influence tutoring of Ganesha Operation to the student National Examination achievement SMA Negeri 7 Banjarmasin Academic Year 2014/2015. Population and sample in this research is students of SMA Negeri 7 Banjarmasin who follow tutoring Ganesha Operation, the number of students are 81 students and using technique sampling jenuh. Primary data obtained through observation in the field and spread questionnaire, secondary data obtained from study of library and study of document. The method of this research is quantitative method and correlation research approach. Analysis technique is percentage technique and product moment correlation. The research result shows that there is no significant influence between tutoring Ganesha Operation to the National Examination achievement, score rxy -0,291 which less than score between 0,000 – 0,200 with lowes interpretation (no correlation) and the hypotheses rejected. The conclusion from the research result is that not only variable X (tutoring Ganesha Operation) which can be used as predictor for variable Y (National Examination achievemet).Keyword: Tutoring of Ganesha Operation, National Examination Achievement.